Comparative life cycle assessment of silver nanoparticle synthesis routes1. Issue 4 (30th August 2015) - Pourzahedi, Leila; Eckelman, Matthew J.
<x xml:space="preserve">Abstract</x> Life cycle assessment of eight nanosilver synthesis routes, both physical and chemical, with results scaled by mass and function.